Simultaneous Esophageal and Tracheal Obstructions Caused by a Pair of Magnetic Beads in a Child: A Case Report - Ren, Huan; Shi, Dong; Gu, Zhaowei; Cao, Zhiwei (Frontiers in Pediatrics, 2021)
Esophageal and tracheal foreign body ingestion trigger common pediatric emergencies. In this case report, we describe a pediatric patient with simultaneous tracheal and esophageal obstruction caused by foreign bodies. A child aged 2 years and 1 month swallowed a pair of metallic magnetic beads at the same time; one bead entered the trachea and the other bead entered the esophagus. We suspected that the two magnetic beads were mutually attracted and thus became trapped in their respective lumina. The tracheal foreign body was uneventfully removed; this dislodged the esophageal foreign body, which was then excreted. There were no serious complications in the present case, but parents and medical personnel should be mindful of the potential hazards associated with ingestion of multiple magnetic foreign bodies. A high index of suspicion is appropriate. Investigations must be carefully planned. Treatment should not be delayed; the consequences of delay may be serious.